She Came Down from Heaven The Storied Propositions of Piers Plowman 's Holy Church - Schrock, Chad D. 1978- (2016)
Currently, we read the late 14th-century Middle English poem Piers Plowman as a form that fails to keep the promises it makes, and its form does make promises, most overtly in its initial fantasy of perfect and lucid meaning embodied in the figure of Holy Church. This article will argue that Holy Church's propositional discourse at the beginning of the poem actually declares itself penultimate and promises with all its authority the messy and muddled epistemological adventure that follows. Holy Church makes promises she keeps by establishing the relationship between the poem's unresolved quests for truth and a hermeneutics, within and without the poem, that can salvage and sanction the partial results of those quests. Allegorically she represents the love of the incarnate Christ; for her, this 'love' means experiencing truth through an incarnate moral self, a desiring life in time. Implicit in her embodied definition of divine love is a temporal structure: a desire for how to 'do best' honed through a history of privation, whetted through cycles of partial and inadequate resolution, ever incomplete on earth but operating in hope of heavenly clarity. The love she authorises is a principle not just of moral praxis but of open narrative form, after the example of Augustine.